Comparison of ACR 1990 and ACR 2010 classification criteria in fibromyalgia syndrome - Gür, Mustafa; Gülkesen, Arıf; Akgol, Gurkan (My University, 2019)
Purpose of this study is to compare the American College of Rheumatology (ACR) 1990 and ACR 2010 classification criteria in fibromyalgia syndrome. Fifty-one patients with fibromyalgia syndrome (FMS) and 50 control patients were included in the study. Patients with FMS were diagnosed by a specialist, and ACR 1990 or ACR 2010 classification criteria were not considered as a necessity. Control group consisted of patients with non-inflammatory pain such as osteoarthritis, periarthritis, regional pain syndrome. Patients were evaluated for ACR 1990 and ACR 2010 criteria, and they were examined for algometry. While ACR 1990 classification criteria had a sensitivity of 0.74, a specificity of 0.88, accuracy of 0.81, ACR 2010 criteria had a sensitivity of 0.78, a specificity of 0.76, and an accuracy of 0.77. In our study, ACR 2010 classification criteria were found to be more sensitive than ACR 1990 classification criteria, but specificity was lower. Besides, the ACR 2010 classification criteria do not require a tender point examination and may be more advantageous in assessing physical and psychological symptoms. It is considered that the classification criteria of ACR 2010 may be more favorable for clinical diagnosis and monitoring of diagnosed disease.
Keywords: Genel ve Dahili Tıp